Antifungal susceptibility profiles and drug resistance mechanisms of clinical Candida duobushaemulonii isolates from China - Chen, Xin-Fei; Zhang, Han; Jia, Xin-Miao; Cao, Jin; Li, Li; Hu, Xin-Lan; Li, Ning; Xiao, Yu-Ling; Xia, Fei; Ye, Li-Yan; Hu, Qing-Feng; Wu, Xiao-Li; et al. (Frontiers in Microbiology, 2022)
Candida duobushaemulonii, type II Candida haemulonii complex, is closely related to Candida auris and capable of causing invasive and non-invasive infections in humans. Eleven strains of C. duobushaemulonii were collected from China Hospital Invasive Fungal Surveillance Net (CHIF-NET) and identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF), VITEK 2 Yeast Identification Card (YST) and internal transcribed spacer (ITS) sequencing. Whole genome sequencing of C. duobushaemulonii were done to determine their genotypes. Furthermore, C. duobushaemulonii strains were tested by Sensititre YeastOneTM and Clinical & Laboratory Institute (CLSI) broth microdilution panel for antifungal susceptibility. Three C. duobushaemulonii could not be identified by VITEK 2. All eleven isolates had high minimum inhibitory concentrations (MICs) to amphotericin B more than 2 μg/mL. One isolate showed a high MIC value of ≥ 64 μg/mL to 5-flucytosine. All isolates were wild type (WT) for triazoles and echinocandins. FUR1 variation may result in C. duobushaemulonii with high MIC to 5-flucytosine. C. duobushaemulonii mainly infects patients with weakened immunity, and the amphotericin B resistance of these isolates might represent a challenge to clinical treatment.